Effects of Newtonian heating and heat generation on magnetohydrodynamics dusty fluid flow between two parallel plates - Farhad Ali; Gohar Ali; Arshad Khan; Ilyas Khan; Elsayed Tag Eldin; Matin Ahmad (Frontiers in Materials, 2023)
Dusty fluids are utilized to minimize heat in systems like gas-freezing systems and nuclear-powered reactors, among other places. The present study aims to investigate the effect of Newtonian heating on dusty fluid flow. Between two parallel plates, the two-phase MHD fluctuating flow of the dusty fluid is considered. The dust particles inside the fluid are thought to be spherical and uniformly distributed. The generation and absorption of heat were also taken into consideration. The motion of the fluid is due to the motion of the right plate with free stream velocity Ut. Partial differential equations are utilized to represent the flow regime. The Poincare-Light Hill Technique is used to find exact solutions. The impact of parameters on the temperature and velocity profiles are shown graphically. Skin friction and rate of heat transfer, two essential fluid parameters for engineers, are also evaluated in tabular form. The velocity of the fluid is shown to decrease with increasing magnetic field. The Newtonian heating phenomena has an effect on the plate’s heating.